The past and present of the juvenile detainees’ pedagogically based treatment in Canada - Peter Ruzsonyi (PedActa, 2017)
The Canadian correctional system as a whole has a diverse array of measures and practices to address issues on the field, these questions are all valid ones in the case of the Nova Scotia Youth Facility an institution that has been a pioneer in the matter of pedagogically treating juvenile delinquency. Despite several legislative and practical changes during its existence, it managed to maintain (and even improve) its unique way of increasing the chances of juveniles under its jurisdiction for a successful reinsertion into society, all the while honouring certain traditions bestowed upon it by the decades of its existence. With this study, we aim to provide a brief introduction to the operation of the Nova Scotia Youth Facility, the historical and legislative background that serves both as the foundation and – in some cases – the obstruction of its goals and methods. During our investigation, we focus on several crucial aspects which underpin the Nova Scotian practice, such as the status of Youth Workers, the unique Restorative Practice carried out within its walls, the group sessions and the changes in the related regulations.